Spatial Properties of Reactive Oxygen Species Govern Pathogen-Specific Immune System Responses - O'Neill, Luke; O'Leary, John (My University, 2020)
Significance: Reactive oxygen species (ROS) are often considered to be undesirable toxic molecules that are generated under conditions of cellular stress, which can cause damage to critical macromolecules such as DNA. However, ROS can also contribute to the pathogenesis of cancer and many other chronic inflammatory disease conditions, including atherosclerosis, metabolic disease, chronic obstructive pulmonary disease, neurodegenerative disease, and autoimmune disease. Recent Advances: The field of ROS biology is expanding, with an emerging paradigm that these reactive species are not generated haphazardly, but instead produced in localized regions or in specific subcellular compartments, and this has important consequences for immune system function. Currently, there is evidence for ROS generation in extracellular spaces, in endosomal compartments, and within mitochondria. Intriguingly, the specific location of ROS production appears to be influenced by the type of invading pathogen (i.e., bacteria, virus, or fungus), the size of the invading pathogen, as well as the expression/subcellular action of pattern recognition receptors and their downstream signaling networks, which sense the presence of these invading pathogens. Critical Issues: ROS are deliberately generated by the immune system, using specific NADPH oxidases that are critically important for pathogen clearance. Professional phagocytic cells can sense a foreign bacterium, initiate phagocytosis, and then within the confines of the phagosome, deliver bursts of ROS to these pathogens. The importance of confining ROS to this specific location is the impetus for this perspective. Future Directions: There are specific knowledge gaps on the fate of the ROS generated by NADPH oxidases/mitochondria, how these ROS are confined to specific locations, as well as the identity of ROS-sensitive targets and how they regulate cellular signaling.
PUBLISHED
cited By 2
Keywords: Reactive oxygen species (ROS); NADPH; Endosome; Mitochondria